Hitchcock on Hitchcock : selected writings and interviews - Hitchcock, Alfred, 1899-1980.; Gottlieb, Sidney (Berkeley : University of California Press, 1995)
Reputations come and go, but Alfred Hitchcock's has remained solidly in place in the pantheon of masters of the cinema. What is less known is that he wrote about the cinema during the course of his life, and his writings are presented here.
My screen memories (1936) -- Life among the stars (1937) -- The woman who knows too much (1956) -- After dinner speech at the Screen Producers Guild dinner (1965) -- Surviving (1977) -- How I choose my heroines (1931) -- Are stars necessary? (1933) -- Women are a nuisance (1935) -- Nova grows up (1938) -- Crime doesn't pay (1938) -- What I'd do to the stars (1939) -- Elegance above sex (1962) -- Gas (1919) -- Why "thrillers" thrive (1936) -- Let 'em play God (1948) -- The enjoyment of fear (1949) -- Master of suspense: being a self-analysis by Alfred Hitchcock (1950) -- Core of the movie -- The chase (1950).
"A bibliography of the writings of Alfred Hitchcock": pages 327-331
Includes bibliographical references (pages 333-334) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Hitchcock, Alfred, -- 1899-1980 -- Interviews; Hitchcock, Alfred, -- 1899-1980; Motion pictures; Motion pictures -- Production and direction; Motion Pictures as Topic; Motion Pictures; Cinéma -- Production et réalisation.; Cinéma.; PERFORMING ARTS -- Film & Video -- Direction & Production; Interviews; Motion pictures; Motion pictures -- Production and direction; Motion pictures; Interviews; Motion pictures; Films